The size of the primordial follicular population and the superovulation response in buffaloes and cows - Ty, Le Van; Son, Hoang Nghia; Hung, Nguyen Mong (Academia Journal of Biology, 2014)
28 ovaries of swamp buffalo foetus and 21 ovaries of local yellow cow foetus in Vietnam have been collected, fixed in Boin-Holland and analysed by routine histologic technique. The pool of primordial follicles of the ovaries have been determined and compared. The size of the pool of primordial follicles of the ovaries of buffaloes was smaller than that of the cows in every recorded foetal development periods. That indicated the faible response of the superovulation in buffalo. It could be a consequence of poor population of the antral follicles due to small pool of primordial follicles.